The Effect of The Use Of Foam Agent and Clam Shell Powder on The Compressive Strength and Absorbency of Concrete - Teuku Ikmal; Sari Indah Manik; Khairullah Yusuf; David Sarana; Amalia Amalia (Malikussaleh University, Aceh, Indonesia, 2022)
A foaming agent is a concentrated solution of surfactant material that must be dissolved in water before mixing with other concrete material. The foaming agent is used to produce lightweight concrete with a density is Â£ 1.900 kg/mÂ³. Using foam agents may affect the compressive strength and absorbency of the concrete. Hence, adding clam shells is expected to improve the compressive strength of the foam concrete. In addition, it is also essential to investigate the effects of utilizing foam agents and clam shells on the density of the foam concrete. Nine concrete mixes namely 1 variation of standard concrete, four variations of concrete mixes with foam agent, and four variations of concrete with foam agent and calm shell have been studied to investigate the parameters.The variation of foam agents in the eight concrete mixes were 5%, 10%, 15%, and 20% by water weight. The last four variations contained clamshell of 5% by weight of fine aggregate. The foam agent wasfoamingduced by mixing with a ratio of water and foam agent of 40:1. The experimental results show that at the variation of 20% foam agent, the density reduced by 34.55% and 26.89% for foam concrete with and without clam shell compared to normal concrete. I contrast, adding clamshell also lowered down the compressive strength of foam concrete by 79.86% and 74.96% for the variations. Meanwhile, the highest absorption rate of 1.65% or increased about 6.45% from normal concrete occurred at a variation foam agent of 15% mixed with clamshell. It was concluded that the use of clam shell in the foam concrete seems to decrease the strength of the foam concrete. However, in terms of density, the use of clam shells benefits foam concrete by lowering the self-weight of concrete.